HUBUNGAN FAKTOR PEKERJAAN DENGAN KELELAHAN KERJA PADA PEKERJA LAPANGAN PROYEK PEMBANGUNAN GEDUNG PT. X DI JAKARTA PUSAT TAHUN 2020 - Kartini Muladame Sejati Sihotang; Rizki Amalia; Fathinah Ranggauni Hardy; Fandita Tonyka Maharani (Jurnal Kesehatan Masyarakat (Undip), 2021)
Work fatigue can be determined by weakening the worker's body, impacting physical and mental performance decreasing. Job-related factors are one of the factors causing work fatigue, such as work duration, physical workload, and mental workload. This study aimed to determine the association between job factors and work fatigue among workers in PT. X building construction site at Central Jakarta. The research method used was quantitative analytic with a cross-sectional design. The research instrument used the IFRC questionnaire, NASA-TLX questionnaire, and pulse oxymeter. This research sample was 109 workers obtained with the accidental sampling technique, and data analyzed using the chi-square test. The results show that 50 workers (45.9%) had experienced a moderate category of work fatigue. The statistical analysis results showed a significant relationship between work duration (p-value = 0.000) and physical workload (p-value = 0.000) with work fatigue. Suggestions that need to be implemented by the company are to regulate work time and overtime according to applicable regulations and divide work shifts.